TEKNIK JITU MEMENANGKAN TAHAPAN TES WAWANCARA KERJA DI PERUSAHAAN - Retno Setya Budiasningrum; Rahmi Rosita; Jajang Setiawan; Dyan Yuliana; Enny Diah Astuti (POLITEKNIK LP3I JAKARTA, 2021)
A job interview is one of the processes in recruitment. This process is very important because the results of the interview will determine the destiny of job seekers. Preparing for a job interview is very important in order to be successful in winning it. Hence, the ability to deal with interview questions is needed by job seekers. The purpose of this community service activity is to help the students of PKBM Ristek Nusantara Jaya Jakarta in increasing their knowledge of job interviews. Implementing this activity started by providing information about preparing for a job interview and showing them some techniques in dealing with interview questions, and it continued with the activity of questions and answers, then ended with the evaluation activity. By having the knowledge of job interviews, participants can prepare themselves and have the confidence to be able to win a job interview successfully.Keyword : Self-preparation, Self-confident, Techniques of job interview